2019
DOI: 10.1002/aenm.201901915
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Induced Surface Reconstruction during Synthesis of High‐Ni Layered Oxides

Abstract: Li-ion batteries (LIBs) are now increasingly used in electric vehicles (EVs) and other large-scale applications, but a bottleneck for their mass adoption is low Li-storage capacity, which is largely constrained by cathodes, typically with a gravimetric capacity equivalent to ≈1/2 that of the graphite anode. Despite much research into candidate cathodes for LIBs, transition metal (TM) layered oxides with a hexagonal structure (space group R3m) have remained dominant over the past three decades. [1,2] In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…Recently, researchers leveraged in situ SXRD and computational modeling to investigate the evolution of non-equilibrium kinetic intermediates and the formation of thermodynamic equilibrium phases during these processes 37 , 38 . Although these studies provide valuable guidance for the predictive synthesis of layered oxides, most of them have focused on examining the impact of structural characteristics during the heating/holding process, such as phase impurity, lattice parameter, crystallite size, Li–TM bond length, and Li + /Ni 2+ mixing 39 41 . The effect of microstrain evolution during the cooling process, especially under rapid quenching, has been largely ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers leveraged in situ SXRD and computational modeling to investigate the evolution of non-equilibrium kinetic intermediates and the formation of thermodynamic equilibrium phases during these processes 37 , 38 . Although these studies provide valuable guidance for the predictive synthesis of layered oxides, most of them have focused on examining the impact of structural characteristics during the heating/holding process, such as phase impurity, lattice parameter, crystallite size, Li–TM bond length, and Li + /Ni 2+ mixing 39 41 . The effect of microstrain evolution during the cooling process, especially under rapid quenching, has been largely ignored.…”
Section: Resultsmentioning
confidence: 99%
“…A robust EEI could suppress the unfavorable parasitic reactions that cause EEI thickening and surface structure degradation. [ 30,39–43 ] Since surface residual lithium could affect the formation of cathode/electrolyte interphase, [ 44 ] it is necessary to evaluate the amount of residual lithium on both samples. As Figure S8 (Supporting Information) shows, the residual lithium amount in the fresh LNO is comparable to that of NMC811.…”
Section: Resultsmentioning
confidence: 99%
“…0.6) to boost capacity while reducing cost. [4] The high-Ni loading, however, leads to lattice collapse during operation at high voltages (> 4.2 V), [5][6][7][8][9] and in the commonly employed polycrystals, anisotropic volume change and the resulted intergranular cracking has been a roadblock to the practical use of high-Ni cathodes. [10][11][12][13][14] In recent studies, long cycling stability was demonstrated in single-crystal high-Ni NMC cathodes.…”
mentioning
confidence: 99%